Alex C.

asked • 05/13/16# Finding variable value in formulas

1. r=2s—2t. Solve for t. When I try to solve, I get (2s—r)/(2) but the book says the answer is s—(r/2)

2. (A/P) = B—1. Solve for B. Again, when I try to solve I get (A/P)+1 and the book says its (a+p)/(p)

More

## 2 Answers By Expert Tutors

Nathan B. answered • 05/13/16

Tutor

5
(20)
Elementary and Algebraic skilled

Okay, I got how the book got its second answer now:

^{A}/

_{P}= B - 1

Multiply both sides by P:

A = BP - P

Add P to both sides:

A + P = BP

Divide both sides by P:

^{A + P}/

_{P}= B

Michael J. answered • 05/13/16

Tutor

5
(5)
Effective High School STEM Tutor & CUNY Math Peer Leader

First, I want to thank you for attempting the problem yourself before asking us for help. Lets compare the answer you got with the book's answer.

1)

When solving for t, you want to isolate the t terms. First, subtract 2s on both sides of the equation.

r - 2s = -2t

Then divide both sides of the equation by -2 to get a coefficient of 1 for t.

(-r + 2s) / 2 = t

when rearranging the terms, you get

(2s - r) / 2 = t

This is the answer you got, which is correct. The book divided each term of the numerator part by 2 (similar to subtracting fractions with common denominator), resulting in

(2s / 2) - (r / 2) = t

s - (r / 2) = t ----> book's answer

The book just put your in a different form. You are correct.

Question 2 is same situation.

## Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

Nathan B.

factor out a 2:

r = 2(s - t)

Divide both sides by 2:

r/2 = s - t

Subtract s from both sides:

r/2 - s = -t

Multiply both sides by -1:

s - r/2 = t

Here's what I think you did:

r = 2s - 2t

r - 2s = -2t

(r - 2s) / -2 = t

(2s - r) / 2 = t

Your answers are essentially the same. Check out what happens when you take your answer and divide by that two in the denominator:

2s/2 - r/2 = t

s - r/2 = t

Now your answer looks exactly like the one in the book--they divided that 2 into the numerator that you have.

05/13/16